Analisis Pengaruh Etos Kerja, Gaya Kepemimpinan, Lingkungan Kerja, dan Komitmen Kerja terhadap Kinerja Karyawan - Selviana, Selviana; Purwati, Astri Ayu; Utariani, Ni Ketut Raka (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study was to examine the effect of work ethic, leadership style, work environment, and work commitment on employee performance at PT. Friends of Indo Utama Pekanbaru. The respondents of this study were 31 employees of PT. Sahabat Indo Utama Pekanbaru with the data collection technique used is a questionnaire. The analytical model used is multiple linear regression models. Meanwhile, to test the hypothesis using statistical tests, namely the F test, determination test (R2), and t test. The results obtained indicate that work ethic has a negative and insignificant effect on employee performance. Leadership style has a positive and significant effect on employee performance. The work environment has a positive and significant effect on employee performance. Work commitment has a positive and insignificant effect on employee performance.